A ADMINISTRAÇÃO DA EXTENSÃO UNIVERSITÁRIA NAS IES PARTICULARES: LIMITES E POTENCIALIDADES NA VISÃO DOS GESTORES - Silva, Luciane Duarte da (2012)
The current dissertation deals with managers vision towards universitarian extension at the superior teaching institutions in the Great ABC area. The theme revision indicates that the universitarian extension is directly dependent on the political vision of the institution which belongs to. There are, hence, several practical and conceptual patterns. Originally, it has adopted the character of free-opened courses to the society, previously known as service rendered, advisements, community action, social welfare work and presently it has been discussed the universitarian extension upon social development perspective and mediator teaching and research. The leading task question is: In what manner has the universitarian extension been managed at the private IESes? By this general aim, the research attempts for the universitarian extension administration, focusing, the private superior teaching institutions at the Great ABC area. To help in this general aim reaching, two specific objectives have been delimited: (a) Identifying the political conceptions as well as the extension service practices mentioned by the IESes. (b) Analysing the manager vision on the administration of the extension. The collected information will be examined by the point of view of three administrative dimensions, namely: human, material and systematics. It is concerning qualitative, exploratory and descriptive investigation. The documental and semi structured research are parts of collected information which will give a subsidy to the final examination. The social scientific contribution discussed on this task is the reflection towards the boundaries and potentialities about the administration of extension before the theme s dialogues nowadays.